2017
DOI: 10.11646/phytotaxa.294.1.1
|View full text |Cite
|
Sign up to set email alerts
|

A revision of the genus Syagrus (Arecaceae)

Abstract: No part of this publication may be reproduced, stored, transmitted or disseminated, in any form, or by any means, without prior written permission from the publisher, to whom all requests to reproduce copyright material should be directed in writing.This authorization does not extend to any other kind of copying, by any means, in any form, and for any purpose other than private research use. ......................................................................................................................… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
76
0
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(86 citation statements)
references
References 9 publications
1
76
0
9
Order By: Relevance
“…The wide habitat variation and the occurrence of ancient lineages of Attalea in TRFs and recently diversified sister clades in seasonally dry ecosystems suggest that Attalea successfully colonized the younger dry ecosystems in South America, such as the Neotropical savanna, known as Cerrado (Freitas et al, ). In fact, Neotropical savanna and seasonally dry tropical forests are now the centres of distribution of Attalea , Syagrus and Butia , indicating their great adaptive potential of survival and diversification in seasonal ecosystems (Freitas et al, ; Noblick, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The wide habitat variation and the occurrence of ancient lineages of Attalea in TRFs and recently diversified sister clades in seasonally dry ecosystems suggest that Attalea successfully colonized the younger dry ecosystems in South America, such as the Neotropical savanna, known as Cerrado (Freitas et al, ). In fact, Neotropical savanna and seasonally dry tropical forests are now the centres of distribution of Attalea , Syagrus and Butia , indicating their great adaptive potential of survival and diversification in seasonal ecosystems (Freitas et al, ; Noblick, ).…”
Section: Discussionmentioning
confidence: 99%
“…Increases in diversification that coincide with seasonally dry ecosystem development, in fact, have been reported for Neotropical palms, such as Astrocaryum (Roncal, Kahn, Millan, Couvreur, & Pintaud, 2013) and Attalea (Freitas et al, 2016). Moreover, niche conservatism leads to low lineage exchange between distinct habitats (Wiens et al, 2010), which might also contribute to the turnover patterns (Eiserhardt, Svenning, Baker, Couvreur, & Balslev, 2013 (Meerow, 2006), whereas Attalea and Syagrus occur in a range of habitats from TRFs to dry xeric shrublands in South America (Henderson, Galeano, & Bernal, 1995;Noblick, 2017 (Freitas et al, 2016;Noblick, 2017).…”
Section: Different Lineage Composition In Seasonally Dry Palmsmentioning
confidence: 92%
“…However, the S. oleracea distribution overlaps with S. cearensis from Brazil’s Northeast region and at one time they were considered to be the same species (Glassman 1987, Noblick 2004, 2017). …”
Section: Discussionmentioning
confidence: 99%
“…The following is meant to be a supplement to a revision of Syagrus (Noblick 2017). Palm leaflet anatomy has been useful in identification and has been used to suggest systematic relationships in the family.…”
Section: Introductionmentioning
confidence: 99%
“…Among almost 100 weevils known from Burmese amber to date, and many thousands of Coleoptera, no additional specimens of Curculionidae have come to light, throwing further doubt on the origin of the two members of Curculionidae described thus far from Burmese amber. [62,63]. Based on a review of the literature and extensive fieldwork, he found that the most abundant weevils visiting flowers of Syagrus coronata (Mart.)…”
Section: The Burmese Amber Weevil Fauna (Rolf Oberprieler)mentioning
confidence: 99%